Fecal Microbiome Changes and Specific Anti-Bacterial Response in Patients with IBD during Anti-TNF Therapy - Schierova, Dagmar; Roubalova, Radka; Kolar, Martin; Stehlikova, Zuzana; Rob, Filip; Jackova, Zuzana; Coufal, Stepan; Thon, Tomas; Mihula, Martin; Modrak, Martin; Kverka, Miloslav; Bajer, Lukas; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are chronic disorders of the gastrointestinal tract that have been linked to microbiome dysbiosis and immune system dysregulation. We investigated the longitudinal effect of anti-TNF therapy on gut microbiota composition and specific immune response to commensals in IBD patients. The study included 52 patients tracked over 38 weeks of therapy and 37 healthy controls (HC). To characterize the diversity and composition of the gut microbiota, we used amplicon sequencing of the V3V4 region of 16S rRNA for the bacterial community and of the ITS1 region for the fungal community. We measured total antibody levels as well as specific antibodies against assorted gut commensals by ELISA. We found diversity differences between HC, Crohn's disease, and ulcerative colitis patients. The bacterial community of patients with IBD was more similar to HC at the study endpoint, suggesting a beneficial shift in the microbiome in response to treatment. We identified factors such as disease severity, localization, and surgical intervention that significantly contribute to the observed changes in the gut bacteriome. Furthermore, we revealed increased IgM levels against specific gut commensals after anti-TNF treatment. In summary, this study, with its longitudinal design, brings insights into the course of anti-TNF therapy in patients with IBD and correlates the bacterial diversity with disease severity in patients with ulcerative colitis (UC).
Keywords: houby; idiopatické střevní záněty; Feces; RNA, Ribosomal, 16S; metagenomika; stupeň závažnosti nemoci; Leukocytes, Mononuclear; střevní mikroflóra; Antibodies; protilátky; Male; biodiverzita; Interleukin-17; leukocyty mononukleární; inflammatory bowel disease; mužské pohlaví; studie případů a kontrol; Adult; Fungi; tumor necrosis factor-α; Gastrointestinal Microbiome; microbiome; ženské pohlaví; RNA ribozomální 16S; feces; Humans; mycobiome; biological therapy; inhibitory TNF; interleukin-17; Biodiversity; Metagenomics; Tumor Necrosis Factor Inhibitors; dospělí; Inflammatory Bowel Diseases; Female; Severity of Illness Index; lidé; Case-Control Studies